Policy Analysis of Cleanliness, Health, Safety, and Environmental Sustainable (CHSE) in Restaurant Service Business in Pare Pare City - South Sulawesi Province - Wim J Winowatan; Rita Rita; Herry Rachmat Widjaja; Andi Ade Zulkifli; Darwis Darwis (Universitas Dharma Wacana, 2022)
This study aims to determine the implementation of government policies and determine the perception of tourism business actors with the government's policy regarding the CHSE program during the pandemic period in the city of Parepare. This research is a type of qualitative research, with data collection techniques using interviews, documentation and triangulation. Using a research instrument, namely interview guidelines. The data were analyzed using qualitative descriptive analysis techniques, through the stages of data reduction, data presentation and drawing conclusions. The results of the study indicate that implementation of government policies regarding the CHSE program during the pandemic in the city of Pare-Pare has not been carried out properly and optimally so that this makes tourism service business actors learn and find out for themselves about the CHSE program, restaurant service business actors in particular, only following the recommendations of health protocols, this is due to the lack of socialization and coordination provided by the government. The perception of tourism business actors with the government's policy on the CHSE Program raises good and positive things, but because there is no socialization about policies This makes restaurant service business actors and guests or consumers have different perceptions and positive and negative views, the existence of government policies regarding the CHSE Program is not well known by restaurant service businesses and the public so they choose to find out for themselves. and practice it yourself.